2006
DOI: 10.1039/b516245a
|View full text |Cite
|
Sign up to set email alerts
|

Probing the competition between secondary structures and local preferences in gas phase isolated peptide backbones

Abstract: Combining laser desorption with a supersonic expansion together with the selectivity of IR/UV double resonance spectroscopy makes it possible to isolate and characterise the gas phase of remarkable backbone conformations of short peptide chains mimicking protein segments. A systematic bottom-up approach involving a conformer-specific IR study of peptide sequences of increasing sizes has enabled us to map the spectral signatures of the intramolecular interactions, which shape the peptide backbone, in particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
343
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(363 citation statements)
references
References 111 publications
(268 reference statements)
19
343
0
Order By: Relevance
“…A truly bottom-up understanding of polypeptide structure and dynamics would greatly benefit from a first-principles quantum-mechanical treatment, as it becomes increasingly more feasible for large systems and long time scales. In particular, quantum-mechanical simulations in vacuo are invaluable for a quantitative understanding of the intramolecular forces that largely control the structure, stability and (un) folding dynamics of polypeptides.Recent progress in the experimental isolation and spectroscopies of gas-phase biological molecules has lead to increasingly refined vibrational spectra for the structure of peptides and proteins [4][5][6]. In fact, in vacuo proteins frequently preserve the secondary structure (helices and sheets) observed in solution, and recent results [7] have shown that even tertiary and quaternary structures can be transferred into the gas phase.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A truly bottom-up understanding of polypeptide structure and dynamics would greatly benefit from a first-principles quantum-mechanical treatment, as it becomes increasingly more feasible for large systems and long time scales. In particular, quantum-mechanical simulations in vacuo are invaluable for a quantitative understanding of the intramolecular forces that largely control the structure, stability and (un) folding dynamics of polypeptides.Recent progress in the experimental isolation and spectroscopies of gas-phase biological molecules has lead to increasingly refined vibrational spectra for the structure of peptides and proteins [4][5][6]. In fact, in vacuo proteins frequently preserve the secondary structure (helices and sheets) observed in solution, and recent results [7] have shown that even tertiary and quaternary structures can be transferred into the gas phase.…”
mentioning
confidence: 99%
“…Recent progress in the experimental isolation and spectroscopies of gas-phase biological molecules has lead to increasingly refined vibrational spectra for the structure of peptides and proteins [4][5][6]. In fact, in vacuo proteins frequently preserve the secondary structure (helices and sheets) observed in solution, and recent results [7] have shown that even tertiary and quaternary structures can be transferred into the gas phase.…”
mentioning
confidence: 99%
“…And as one might expect, the importance of the peptide-peptide interaction has motivated a good deal of prior theoretical scrutiny [18][19][20][21][22][23][24] . Due to the delicacy involved in comparisons of different sorts of geometries, with differing origins of stability, it would be injudicious to base any decisions of relative stability on any but high-level correlated calculations, of which there have been several performed in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…5 Conformer selective IR spectroscopy in the gas phase has been applied to various interesting systems, such as isolated or paired nucleobases, 6 to the amino-acids phenylalanine 4 and tryptophan, 7,8 to beta-sheet model systems 9 and other small peptides. 10,11 Most of these experiments have been performed using laser systems that cover the near-and mid-IR and are limited to wavelengths shorter than about 7 mm. In this range X-H (X ¼ C, O, N) and CQO stretching vibrations are probed and the experiments provide an insight into the conformational arrangement, as those vibrational transitions exhibit shifts in absorption frequency and changes in intensity in the presence of, for instance, intramolecular hydrogen bonds or solvating molecules.…”
Section: Introductionmentioning
confidence: 99%